2017
DOI: 10.1002/cam4.1136
|View full text |Cite
|
Sign up to set email alerts
|

Hormone factors play a favorable role in female head and neck cancer risk

Abstract: Due to lower female incidence, estimates of exogenous and endogenous hormonal factors in head and neck cancers (HNCs, comprising cancers of the oral cavity, oropharynx, hypopharynx, and larynx) among women have been inconsistent and unable to account for key HNC risk factors. We pooled data from 11 studies from Europe, North America, and Japan. Analysis included 1572 HNC female cases and 4343 controls. Pooled odds ratios (ORs) estimates and their 95% confidence intervals (CIs) were calculated using multivariat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 48 publications
2
41
0
Order By: Relevance
“…27 Additionally, estrogen may lend a protective effect (both endogenous and exogenous in the case of hormone replacement therapy) even mitigating the effects of tobacco and alcohol use. 28 Women who experience menopause (either natural or surgically induced) at a younger age (<52 y) also have a higher risk of head and neck cancer, which in part could be related to the loss of the protective effects of estrogen. 28 One large British study examining inequalities in larynx cancer in England and Wales between 1991 and 2006 found the 5-year OS in women to be 8% lower than in men.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Additionally, estrogen may lend a protective effect (both endogenous and exogenous in the case of hormone replacement therapy) even mitigating the effects of tobacco and alcohol use. 28 Women who experience menopause (either natural or surgically induced) at a younger age (<52 y) also have a higher risk of head and neck cancer, which in part could be related to the loss of the protective effects of estrogen. 28 One large British study examining inequalities in larynx cancer in England and Wales between 1991 and 2006 found the 5-year OS in women to be 8% lower than in men.…”
Section: Discussionmentioning
confidence: 99%
“…28 Women who experience menopause (either natural or surgically induced) at a younger age (<52 y) also have a higher risk of head and neck cancer, which in part could be related to the loss of the protective effects of estrogen. 28 One large British study examining inequalities in larynx cancer in England and Wales between 1991 and 2006 found the 5-year OS in women to be 8% lower than in men. 29 Ellis et al reported lower 5-year OS in women across all three time periods of 1991-1995, 1996-2000, and 2000-2006.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a higher risk of HNSCC is associated with menopause onset before 52 years of age. 75 Furthermore, oestrogen-related and progesterone-related factors interact with common risk factors, such as smoking and alcohol, that are known to biologically affect female hormone pathways. Indeed, tobacco smoking increases oestrogen catabolism, 76 while liver metabolism, affected by alcohol drinking, is involved in oestrogen homoeostasis.…”
Section: Stratification Of Hpv-related Hnscc By Sexmentioning
confidence: 99%
“…77 The higher oestrogen levels present in alcohol drinkers can act synergistically with the presence of endogenous/ exogenous hormones to decrease the HNSCC risk in women. 75 It is most likely, however, that there are intrinsic biochemical and molecular differences between female and male cells that have an impact on tumorigenesis, independently of sex hormones. For example, differences in the global demethylation pattern of induced pluripotent stem cells have been observed between males and females, 78 and it is well established that HPV modifies the epigenetic landscape of host cells by upregulating DNA methyltransferase 1 (DNMT1).…”
Section: Stratification Of Hpv-related Hnscc By Sexmentioning
confidence: 99%
“…Interestingly, one of these hub miRNAs, miR-181a-5p, and the 7 co-expressed miRNAs, target mRNAs associated with the estrogen receptors signaling pathway. GT catechin have been shown to both inhibit or stimulate in a concentration dependent manner, different components of the estrogen receptor signaling pathway including ER alpha itself 55 Estrogen receptor and estrogen levels are thought to be important in head and neck SCC outcomes 56 . The epidermal growth factor receptor is activated during carcinogensis in many head and neck cancers and is thought to be a key driver of that state 57 .…”
Section: Discussionmentioning
confidence: 99%